Pengaruh video animasi dan e-leaflet terhadap perilaku deteksi dini stunting - Fathinatusholihah Fathinatusholihah; Elvi Destarianiy; Rolita Efriani; Demsa Simbolon; Elly Wahyuni (Poltekkes Kemenkes Aceh, 2024)
Background: The incidence of stunting among children under five in Indonesia still exceeds the target set by WHO. Efforts to increase cadres knowledge about stunting by providing health education using video media and e-leaflets. Information conveyed using media will speed up comprehension by 50%.Objectives: This study aims to measure the effect of education through animated video media and e-leaflets on early stunting detection behavior.Methods: This research used a Quasi Experimental pre-post test design with control group. The research was conducted at the Community Health Center in Bengkulu city from December 2023 to February 2024. The treatment given to the intervention group used an animated video media and to the control group used an e-leaflet media. With a sample of 36 people. Research data was collected during the pre-test and post-test. Data analysis was carried out using the Wilcoxon Signed Rank Test and the Mann Whitney Test.Results: The research results show the influence of animated video media on the knowledge, attitudes and skills of posyandu cadres in early detection of stunting (p-value <0,05).Conclusion: Animated video media and e-leaflets can increase the knowledge, attitudes and skills of posyandu cadres to detect stunting, but with animated video media changes in knowledge, attitudes and skills of posyandu cadres are higher.